Epidemiological study on admission of infectious diseases in pediatrics department of a tertiary care hospital, Jharkhand, India - Murmu, Nisha; ., Pushpa; Kujur, Anit; Sagar, Vidya; Kashyap, Vivek (International Journal Of Community Medicine And Public Health, 2020)
Background: Infectious diseases have a major contribution in the mortality and morbidity among children in India. The aim of our study was to assess the infectious diseases and the sociodemographic characteristics along with the assessment of awareness on mode of transmission of these diseases among the family members. Methods: This was a cross-sectional study done in Department of Pediatrics, RIMS, Ranchi, for a period of 6 months by consecutive sampling. Pre-tested, semi structured questionnaire was used for data collection and analysed in SPSS version 20. Results: A total of 220 children were included in the study. Majority of patients (60%) comprised of under 5 age group with male predominance (55%), with 84.1% children fully immunized, among which 54.1% were institutional deliveries and approx. 85.9% children were breast fed for more than 6 months. Malaria, being an endemic disease of Jharkhand affected maximum children (38.2%). Sanitation, (toilet facilities) was about 27% and hand hygiene was only 5% in the family members of the patients admitted. Thus lack of awareness and poor hand hygiene was an important finding in our result. Conclusions: Health education among the community should be the prime concern for the reduction of the diseases.